1985
DOI: 10.1007/bf00199228
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of methotrexate to IgG antibodies and their F(ab)2 fragments and the effect of conjugated methotrexate on tumor growth in vivo

Abstract: Methotrexate (MTX) was first conjugated to antibovine serum albumin IgG (antiBSA) or its F(ab)2 fragment to define conditions for retention of drug and antibody activity. With identical drug: protein molar ratios, incorporation in the F(ab)2 fragment was lower than in intact antiBSA, an observation consistent with analysis of the number of lysine residues (22 in F(ab)2 compared to 40 in antiBSA). In either case, up to approximately 10 mol MTX could be incorporated per mol protein, with recovery of 70% of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…Studies in experimental animals with some other conjugates, particularly daunomycin (Baldwin et al, 1986) and vindesine (Rowland et al, 1985(Rowland et al, , 1986 have shown tumour localisation of drug and/or antibody moieties of conjugates in experimental studies. Such conjugates can show increased therapeutic effectiveness and/or reduced toxicity in experimental systems (Kanellos et al, 1985;Kulkarni et al, 1985;Rowland et al, 1985Rowland et al, , 1986Smyth et al, 1986;Baldwin et al, 1986) and the interpretation here is that this is due to altered biodistribution and/or tumour localisation of the conjugated drug. These conjugates are clearly candidates for clinical evaluation.…”
Section: Disc1 Jssionmentioning
confidence: 88%
“…Studies in experimental animals with some other conjugates, particularly daunomycin (Baldwin et al, 1986) and vindesine (Rowland et al, 1985(Rowland et al, , 1986 have shown tumour localisation of drug and/or antibody moieties of conjugates in experimental studies. Such conjugates can show increased therapeutic effectiveness and/or reduced toxicity in experimental systems (Kanellos et al, 1985;Kulkarni et al, 1985;Rowland et al, 1985Rowland et al, , 1986Smyth et al, 1986;Baldwin et al, 1986) and the interpretation here is that this is due to altered biodistribution and/or tumour localisation of the conjugated drug. These conjugates are clearly candidates for clinical evaluation.…”
Section: Disc1 Jssionmentioning
confidence: 88%
“…In (Deguchi et al, 1986;Fung et al, 1979;Garnett et al, 1983;Kanellos et al, 1985;Kulkarni et al, 1985;Tsuro et al, 1980) and is probably due to the stearic interference of the macromolecule with the binding of the pteridine moiety of the methotrexate to the active site of the enzyme (Baker, 1969 (Bertino, 1963) (Hurwitz et al, 1979;Johnson et al, 1981;Kulkarni et al, 1985). In the experiments reported in this paper, non-immune IgG-methotrexate conjugates were significantly less effective than either methotrexate alone or antibody-methotrexate conjugates in reducing the cell number ( Figure 2) and causing in the release of 5'Cr from cells in vitro (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In the early days of protein-drug conjugates, toxins such as ricin were used [31]. The chemotherapy drugs doxorubicin [32,33], methotrexate [34], vinca alkaloids [35], etc. , have also been conjugated to antibodies.…”
Section: Cytotoxic Drugs and Mechanisms Of Actionmentioning
confidence: 99%